The kinetics of endosome processing - Legalatladi, Seetsela (Division of Biomedical Engineering, 2018)
The present thesis looks at the behaviour of internalised cell surface-derived membrane marker in comparison with the behaviour of endocytosed HRP (horse-radish peroxidase) as a fluid-phase contents marker. The pooling and/or segregation in the endosome was measured by determining co-localization with HRP. Colocalization of the two markers in the endosome is studied by using the ability of HRP to catalyse the crosslinking of membrane marker in endosomes with DAB (3,3'-diaminobenzidine), rendering the membrane marker detergent insoluble. To study the kinetic behaviour of membrane marker, radioactive galactose was covalently bound to cell-surface glycoconjugates on mouse macrophage-cells, P388D₁, as catalysed by galactosyltransferase. This provided a general membrane marker. After endocytosis-derived redistribution of membrane marker between the cell surface and endosomal membrane, a steady state was established with about 16% of the label on internal membranes. The bulk of the label on the cell surface was removable by subsequent treatment with β-galactosidase.